Critical Issues in Head and Neck Oncology Key Concepts from the Eighth THNO Meeting - Vermorken, Jan B.; Budach, Volker; Leemans, C. René; Machiels, Jean-Pascal; Nicolai, Piero; O'Sullivan, Brian (Springer Nature, 2023)
This is an open access book. With a wealth of exciting data emerging in this rapidly evolving field this book will review the state-of-the-art knowledge with emphasis on multidisciplinary decision and management of head and neck cancer. The book provides significant detail on a wide range of topics including: the role of new targets for treatment, immunotherapy, resistance mechanisms, standardizing molecular profiling programs, and new methods to guide therapeutic approaches. In addition different disease situations are addressed including different treatment approaches in primary disease and in recurrent and/or metastatic disease as well as new developments in pathology, surgery and reconstruction techniques, new systemic therapies in salivary gland cancer, and supportive care and follow-up. All disciplines involved in the treatment of head & neck cancer are covered with a focus on translation into daily practice. The 8th-THNO is designed for medical oncologists, head and neck surgeons, radiation oncologists, otolaryngologists, and other medical professionals involved in the treatment of patients with head and neck cancer.